A new fucosylated glycosaminoglycan containing disaccharide branches from Acaudina molpadioides: Unusual structure and anti-intrinsic tenase activity. (1st October 2020) - Mao, Hui; Cai, Ying; Li, Shanni; Sun, Huifang; Lin, Lisha; Pan, Ying; Yang, Wenjiao; He, Zhicheng; Chen, Ru; Zhou, Lutan; Wang, Weili; Yin, Ronghua; et al.
Highlights: A novel FG (AmFG) were extracted from sea cucumber Acaudina molpadioides . The structures of eight oligosaccharides from depolymerized AmFG were determined. AmFG branched with unusual disaccharide GalNAc-α1, 2-Fuc, besides monosaccharides. The anticoagulant and anti-iXase activities of AmFG and oligomers were discussed. Abstract: A fucosylated glycosaminoglycan (AmFG) was extracted from the sea cucumber Acaudina molpadioides . And a series of oligosaccharides were purified from the size-homogeneous fractions, which were prepared from the β-eliminative depolymerized AmFG. According to "bottom-up" strategy, the precise structure of AmFG was elucidated by analyzing the structures of these purified oligosaccharides, combining with NMR analysis of its free-radical depolymerized product. It contained a CS-E-like backbone, and each GlcUA was branched with a mono- or di-sulfated fucose (Fuc) at O -3. Intriguingly, besides two types of monosaccharide branches, Fuc2S4S (60 %) and Fuc4S (25 %), that were common in FG, AmFG also contained an unusual disaccharide branch GalNAc-α1, 2-Fuc3S4S (15 %); this is the first report of such a structure in a glycosaminoglycan. Biological assays indicated that native AmFG and its oligosaccharides had potent anticoagulant and intrinsic tenase (iXase) inhibitory activities in a chain length-dependent manner. For these oligosaccharides, octasaccharide was the minimum structural fragment for potent anti-iXase activity, and the disaccharide branch might enhance this activity.